¿Quién se robó mi propiedad? el tratamiento de los recursos naturales mineros a la luz de las teorías de dominio público y su aplicación en el Perú - Mutsios Ramsay, Milagros (2019)
The way in which the private property regime is structured often delimits the way in which a society is organized. In the mining aspect, ownership of natural resources is usually the main reason for the proper functioning of the system or endless disputes between native communities and state agencies.In this sense, in order to better understand how the pubic domain system is structured on natural resources in our country, Milagros Mutsios explains in this article the four main public domain theories of natural resources and delves into the various concepts that influence the adoption or operation of each of these.